A pilot study of the effects of crocin on high‐density lipoprotein cholesterol uptake capacity in patients with metabolic syndrome: A randomized clinical trial. (5th October 2021) - Saberi‐Karimian, Maryam; Safarian‐Bana, Hamideh; Mohammadzadeh, Elham; Kazemi, Tooba; Mansoori, Amin; Ghazizadeh, Hamideh; Samadi, Sara; Nikbakht‐Jam, Irandokht; Nosrati, Mina; Ferns, Gordon A.; Esmaily, Habibollah; Aghasizadeh, Malihe; et al.
Abstract: A randomized clinical trial high‐density lipoprotein (HDL) cholesterol uptake capacity (CUC) is reduced in patients with metabolic syndrome (MetS). We have assessed the effect of crocin supplementation on HDL CUC in patients with MetS. Forty‐four subjects with MetS were randomly allocated to one of two groups: one group received placebo and the other group received crocin at a dose of 30 mg (two tablets of 15 mg per day) for 8 weeks. Serum biochemical parameters were measured using an AutoAnalyzer BT3000 (BioTechnica). The modified CUC method is a cell free, simple, and high‐throughput assay that used to evaluate HDL CUC of serum samples. The decision tree analysis was undertaken using JMP Pro (SAS) version 13. The mean age of the crocin and placebo groups were 38.97 ± 13.33 and 43.46 ± 12.77 years, respectively. There was a significant increase in serum HDL CUC in the crocin group compared to that of the placebo group in patients with MetS ( p ‐value< 0.05). The decision tree analysis showed that serum HDL functionality was more important variable than HDL‐C level in predicting patients with hypertension at baseline ( p ‐value < 0.05). Crocin administration (30 mg for a period of 8 weeks) was found to improve serum HDL CUC in patients with MetS. Trial registration: IRCT2013080514279N1